IMPLEMENTASI KEGIATAN KEISLAMAN DALAM MENANAMKAN NILAI-NILAI RELIGIUS PADA PESERTA DIDIK DI UPT SPF SDN 57 ORO GADING KABUPATEN BULUKUMBA - Hesti Ananta; Samsuriadi; Ainun Jariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study is motivated by the importance of instilling religious values in students to shape individuals who are faithful and possess noble character. However, in practice, there are still students who lack discipline in performing religious activities and have not fully applied religious values in their daily lives. Therefore, effective efforts are needed through Islamic activities in schools. This study aims to determine the implementation of Islamic activities in instilling religious values in students at UPT SPF SDN 57 Oro Gading, Bulukumba Regency. The type of research used is qualitative research with a descriptive approach. The research subjects include the principal, teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and conclusion drawing, while data validity was ensured through triangulation. The results show that Islamic activities such as Duha prayer and congregational Zuhr prayer have been carried out routinely and have a positive impact on instilling students’ religious values. This is indicated by increased awareness in worship, discipline, responsibility, and better behavior. In addition, there are supporting factors such as a conducive school environment and adequate facilities, as well as inhibiting factors such as external environmental influences and student social interactions. Thus, it can be concluded that the implementation of Islamic activities is effective in instilling religious values in students.